(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The quality of tillage with traditional plowing plows does not meet the agrotechnical requirements. The purpose of the research is to develop a plow for smooth, rowless plowing. A plow for smooth plowing is proposed, which contains twin screw housings, first-row colliders, rear screw right- and left-turning plow housings, second-row colliders. An experimental sample of a plow for smooth plowing was made. The results of field tests of the developed plow are presented. It is established that the quality indicators of the plow fully comply with agrotechnical requirements. At the same time, the degree of reduction in fuel consumption compared to the existing plow is 21, 26 %.